2021
DOI: 10.1111/cod.13993
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis from black rubber in firefighters' masks: A case series

Abstract: 9. Hausen BM, Beyer W. The sensitizing capacity of the antioxidants propyl, octyl, and docecyl gallate and some related gallic acid esters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…5 The use of respiratory protective equipment has been shown to impair the skin barrier as a result of increased temperature and humidity from expiration with an occlusive effect of masks. 6 In conclusion, we report an unusual case of occupational facial allergic contact dermatitis to IPPD present in his professional gas F I G U R E 1 (A) Erythematous and scaly, pruriginous dermatitis on the face (B) Policeman's gas mask. mask.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…5 The use of respiratory protective equipment has been shown to impair the skin barrier as a result of increased temperature and humidity from expiration with an occlusive effect of masks. 6 In conclusion, we report an unusual case of occupational facial allergic contact dermatitis to IPPD present in his professional gas F I G U R E 1 (A) Erythematous and scaly, pruriginous dermatitis on the face (B) Policeman's gas mask. mask.…”
Section: Discussionmentioning
confidence: 81%
“…IPPD is chemically related to paraphenylenediamine, with crossreactivity being well described 5 . The use of respiratory protective equipment has been shown to impair the skin barrier as a result of increased temperature and humidity from expiration with an occlusive effect of masks 6 …”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the ratios of products containing PG, parabens and triethanolamine were much higher than those of previous reports. [2][3][4] PG is an uncommon allergen and irritant; however, Patel et al 5 reported that the most common source of PG was topical medicaments, constituting 77.8% of relevant reactions. Parabens were identified in 56% of products in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Gloves are the most frequent source of exposure [17]. N-isopropyl-N-phenylenediamine (found in black rubbers) was implicated as a cause of OACD in first responders wearing rubber protective masks [18 ▪ ,19 ▪ ].…”
Section: Specific Exposuresmentioning
confidence: 99%